Efforts to Improve Mother Skills in LBW (low baby weigh) Baby Care with Approach of Experiential Learning Care (ELC) Method. - Heni Frilasari; Lasiyati Yuswo Yani; Indra Yulianti (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2018)
Low Birth Weight Babies (LBW) are babies born with a body weight of less or equal to 2,500 grams. High levels of stress on parents, especially mothers and low levels of competency, show that parents (mothers) still have the right knowledge of caring for LBW babies. This situation affects the mother's behavior in caring for the baby. Kangaroo method is one of the rights and correct efforts to care for LBW babies because this method provides benefits to increase the temperature of LBW infants. The purpose of this study was to improve maternal skills in care for low birth weight babies with an experiential learning Care approach. The research method used queasy experimental with pre-post test design. The stages in this study start from collecting data through the mother's pre-test skills in the care of low birth weight babies, then providing midwifery interventions through Kangaroo Mother Care with the approach of Experiential Learning Care I, II and III. Next post-test was carried out; data analysis was done through Wilcoxon test with the results of p = 0.003 <Î± = 0.05, meaning that there was an increase in maternal skills in the care of LBW infants with the Experiential Learning Care (ELC) method. The results of this study are expected to be a guide for midwives in midwifery interventions for mothers who have LBW babies. Thus, it will be able to provide maternal skills in the care of LBW babies who are right and correct, so that mothers can care for LBW babies at home properly.